Sexual violence and restorative justice: Legal, social and therapeutic dimensions - Keenan, Marie; Zinsstag, Estelle (Routledge, 2017)
Sexual violence, in all its forms, is a crime for which anecdotal accounts and scholarly reports suggest victims in their great majority do not receive adequate ‘justice’ or redress. The theory and practice of restorative justice is rapidly developing and offers some well-argued new avenues for dealings with crime in general. It has the potential to be extended to cases of sexual violence and a number of small scale programmes are already underway across the world. Restorative Responses to Sexual Violence examines this innovative justice paradigm in more depth in the particular context of sexual trauma and violence in order to establish the empirical realities of restorative justice approaches in cases of sexual violence, and considers how such approaches could be developed adequately in the future. This book is divided into two parts, each representing a key area of research and practice: theoretical and conceptual frameworks, and justice and therapeutic perspectives. This international collection brings together leading expert scholars and practitioners to offer both theoretical and practical perspectives on restorative justice and sexual violence. This book will be of interest to researchers in the field of law, criminology, psychology, social science, social work and psychotherapy, as well as practitioners in the fields of criminal justice, restorative justice and sex offender and victim trauma therapies
Keywords: criminologie; discipline; droit; justice réparatrice; outils; ouvrages de références; science politique et droit; sciences humaines; sociologie; sofia; thématiques; travail social; violences; violences sexuelles

Men's intrusion, women's embodiment: a critical analysis of street harassment - Vera-Gray, Fiona (Routledge, 2017)
Research on violence against women tends to focus on topics such as sexual assault and intimate partner violence, arguably to the detriment of investigating men’s violence and intrusion in women’s everyday lives. The reality and possibility of the routine intrusions women experience from men in public space – from unwanted comments, to flashing, following and frottage – are frequently unaddressed in research, as well as in theoretical and policy-based responses to violence against women. Often at their height during women’s adolescence, such practices are commonly dismissed as trivial, relatively harmless expressions of free speech too subjective to be legislated against. Based on original empirical research, this book is the first of its kind to conduct a feminist phenomenological analysis of the experience for women of men’s stranger intrusions in public spaces. It suggests that intrusion from unknown men is a fundamental factor in how women understand and enact their embodied selfhood. This book is essential reading for academics and students involved in the study of violence against women, feminist philosophy, applied sociology, feminist criminology and gender studies.
Keywords: 2000 à aujourd'hui; 2010-2019; agentivité; angleterre; approches et analyses; corps; discipline; europe; harcèlement de rue; patriarcat; phénoménologie; périodes historiques; régions géographiques; sciences humaines; sociologie; sofia; systèmes d'oppression; thématiques; violences